2013
DOI: 10.1038/ncomms2585
|View full text |Cite
|
Sign up to set email alerts
|

Tuneable enhancement of the salt and thermal stability of polymeric micelles by cyclized amphiphiles

Abstract: Cyclic molecules provide better stability for their aggregates. Typically in nature, the unique cyclic cell membrane lipids allow thermophilic archaea to inhabit extreme conditions. By mimicking the biological design, the robustness of self-assembled synthetic nanostructures is expected to be improved. Here we report topology effects by cyclized polymeric amphiphiles against their linear counterparts, demonstrating a drastic enhancement in the thermal, as well as salt stability of self-assembled micelles. Furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
172
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 155 publications
(178 citation statements)
references
References 55 publications
5
172
1
Order By: Relevance
“…For instance, recent studies demonstrated that thermal stability of polymer micelles increased drastically by a linear-to-cyclic conversion. 7,8 Simulation studies have also suggested an essential role of a loop formation of DNA in a spatial organization of chromosomes. [9][10][11][12][13] These studies point to the critical roles of the cyclization of the polymer chains in various research fields, from materials science to life science.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, recent studies demonstrated that thermal stability of polymer micelles increased drastically by a linear-to-cyclic conversion. 7,8 Simulation studies have also suggested an essential role of a loop formation of DNA in a spatial organization of chromosomes. [9][10][11][12][13] These studies point to the critical roles of the cyclization of the polymer chains in various research fields, from materials science to life science.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in the case of LB multilayers, the heat resistance properties of the cyclic polymers were indicated as reported in previous study. 3,4) The excellent heat stability 13) of cyclic polymers was demonstrated. Based on the results of temperature-controlled out-of-plane XRD, fig.7 shows the disordering behavior of polymers in LB multilayers with heating.…”
Section: Molecular Arrangement Of Organized Molecular Films Of Linearmentioning
confidence: 99%
“…3,4) In this study, the effect on the formation of interfacial molecular films was noted when amphiphilic polymers with different "shape" have been spread to the air/water interface. The merit of this material evaluation in this viewpoint is the fact that components of cell membranes of all including a human corresponds to a linear lipid molecule.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison with linear polymers,c orresponding topological polymers, [2] such as star polymers, [3] cyclic polymers, [4] dendrimers, [5] and hyperbranched polymers, [6] generally provide smaller hydrodynamic volume,l ower solution viscosity,a nd less polymer entanglement in the bulk. These properties are useful in solid materials that can help not only in reducing solvent use as sustainable products but also making the molding process easy because of low melt viscosity.…”
mentioning
confidence: 99%